2014
DOI: 10.1002/ppsc.201400168
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Emulsion Templating of Hybrid Ag/SiO2 Capsules for Antibacterial Applications

Abstract: Silver nanoparticles (NPs) encapsulated in amorphous silica shells are synthesized and evaluated for their antibacterial action using the Gram‐negative Escherichia coli bacterium. These inorganic capsules are synthesized using a new approach that comprises the use of oil‐in‐water‐in‐oil (O/W/O) multiple emulsions to fabricate SiO2 capsules incorporating organically capped Ag NPs. This strategy is explored as a mean to promote the bioadhesion of the microorganisms to the silica rough surfaces while still keepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…This can be attributed to the significantly reduced release rate of Ag + ions by the silica coating layer, which limits the accessibilities of silver ions to cells. [31] To explore the in-depth cell-particle interactions, we conjugated FITC on the particle surface of tAg@SiO 2 and sAg@SiO 2 and compared their cellular internalization efficiency. Fluorescent microscopy and flow cytometry were used to qualitatively and quantitatively measure the fluorescence intensity of cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This can be attributed to the significantly reduced release rate of Ag + ions by the silica coating layer, which limits the accessibilities of silver ions to cells. [31] To explore the in-depth cell-particle interactions, we conjugated FITC on the particle surface of tAg@SiO 2 and sAg@SiO 2 and compared their cellular internalization efficiency. Fluorescent microscopy and flow cytometry were used to qualitatively and quantitatively measure the fluorescence intensity of cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, due to their small size, MNPs can attach to the cell wall of the bacteria or fungi through self-assembly causing cell death [ 46 ]. Additionally, some metals, like silver or zinc, are known for their natural antibacterial activity [ 47 , 48 , 49 ]. However, the MNPs must have the adequate dimension in order to avoid agglomeration/aggregation phenomena, which is related with a significant reduction of the antimicrobial effect.…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
“…It has been found that enzymes often catalyze a broad variety of reactions with strong chemo‐, stereo‐, and regioselectivity properties; however, the use of organic media usually decreases the stability of free enzymes . During recent years, Pickering emulsions in high‐quality aqueous microenvironments have been widely utilized for the enzyme immobilization in organic media . For instance, Wang et al synthesized hollow polymersome‐stabilized colloidosomes for biphasic enzymatic catalysis; the obtained lipase encapsulated inside a polymersome lumen exhibited a high specific activity of 70.8 U mg −1 .…”
Section: Introductionmentioning
confidence: 99%